Negative pole piece and lithium ion battery

By using gradient coating technology on the negative electrode sheet of lithium-ion batteries, combining the negative electrode active materials with high limit compaction density and low limit compaction density, a multi-layer structure is formed, which solves the problems of low rate performance of lithium-ion batteries and easy lithium analysis during the cycle process, and achieves higher energy density and safety performance.

CN119542346AActive Publication Date: 2025-02-28ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411713964.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The current lithium-ion batteries have low rate performance and are easy to remove lithium during the cycle, making it difficult to meet the requirements of energy density and safety performance.

Method used

The negative electrode sheet is designed using gradient coating technology, including a current collector and a negative electrode active material layer arranged on the surface of the current collector. The negative electrode active material is composed of a first negative electrode active material with a high limit compaction density and a second negative electrode active material with a low limit compaction density. The material content is distributed according to a specific gradient to form a multi-layer structure.

Benefits of technology

Through gradient coating technology, the rate performance and cycle stability of lithium-ion batteries are improved, the risk of local black spots or lithium excretion at the anode interface is reduced, and the energy density and safety performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542346A_ABST
    Figure CN119542346A_ABST
Patent Text Reader

Abstract

The invention discloses a negative pole piece and a lithium ion battery, belongs to the technical field of lithium ion batteries, and overcomes the defects that the rate capability of the lithium ion battery in the prior art is relatively low, and lithium is easy to separate out in a circulating process. The negative electrode active material comprises a first negative electrode active material and a second negative electrode active material, the negative electrode active material satisfies the following conditions: A-B = 0.01-0.75 g / cm < 3 >; a is the ultimate compaction density of the first negative electrode active material, and B is the ultimate compaction density of the second negative electrode active material; in the negative electrode active material layer, the negative electrode active material layer comprises n coating layers along the direction far away from the current collector, n is more than or equal to 3 and less than or equal to 10, and n is an integer; along the direction far away from the current collector, the content of the first negative electrode active material in the n coating layers is gradually reduced, and the content of the second negative electrode active material is gradually increased. The problem of local black spots or lithium precipitation of the anode interface can be avoided, and meanwhile the cycling stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to a negative electrode plate and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy, high operating voltage, wide operating temperature range, small size, light weight, and long storage life, and have become a new generation of green and environmentally friendly batteries. With the continuous development of lithium-ion battery related technologies, people have put forward new requirements for energy density, battery life, safety and battery cost.

[0003] With the increase in thickness and compaction density of lithium-ion secondary battery electrode plates, the single-layer mechanical mixing coating method used in the existing technology has been unable to meet the requirements of energy density and safety performance. This type of coating method will cause overpressure on the electrode plates, difficulty in wetting, poor safety, and high risk of thermal runaway.

[0004] Although the emerging double-layer coating technology can solve the above problems, due to the difference in viscosity and surface tension of the two slurries, a large contact / diffusion impedance will be generated between the layers, which is not conducive to the transmission of lithium ions, resulting in reduced rate performance of lithium-ion batteries and easy lithium deposition during the cycle process. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present application is to overcome the defects of low rate performance and easy lithium deposition in the cycle process of lithium-ion batteries in the prior art, thereby providing a negative electrode plate and a lithium-ion battery.

[0006] To this end, this application provides the following technical solutions.

[0007] In a first aspect, the present application provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer disposed on at least one surface of the current collector;

[0008] The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a first negative electrode active material and a second negative electrode active material;

[0009] The negative electrode active material satisfies: AB = 0.01-0.75 g / cm 3 ;

[0010] A is the limiting compaction density of the first negative electrode active material, and B is the limiting compaction density of the second negative electrode active material;

[0011] In the negative electrode active material layer, along the direction away from the current collector, the negative electrode active material layer includes n coating layers, 3≤n≤10, n is an integer;

[0012] Along the direction away from the current collector, the content of the first negative electrode active material in the n coating layers gradually decreases, and the content of the second negative electrode active material gradually increases.

[0013] In a possible implementation, along the direction away from the current collector, among the n coating layers, the thickness of the first layer to the (n+1) / 2th layer gradually decreases, and the thickness of the (n+1) / 2th layer to the nth layer gradually increases; the coating layer close to the current collector is the first layer, and the coating layer away from the current collector is the nth layer;

[0014] Preferably, the thickness h of the (n+1) / 2th layer is (n+1) / 2 = 0, the thickness of the first layer h1 = the thickness of the nth layer h n ;

[0015] Preferably, h1 ≤ 130 μm.

[0016] In one possible embodiment, along the direction away from the current collector, the D50 of the n coating layers is i Gradually increase; D50 i is the average particle size of the negative electrode active material in the i-th layer;

[0017] Preferably, D50 n -D501≤5μm.

[0018] In one possible implementation, XY≥3 mAh / g is satisfied;

[0019] X is the gram capacity of the first negative electrode active material, and Y is the gram capacity of the second negative electrode active material;

[0020] Preferably, the gram capacity of the first negative electrode active material is greater than 355 mAh / g;

[0021] Preferably, the gram capacity of the second negative electrode active material is ≤354 mAh / g.

[0022] In a possible implementation, MN≥2 is satisfied;

[0023] M is the OI value of the first negative electrode active material, and N is the OI value of the second negative electrode active material;

[0024] Preferably, the OI value of the first negative electrode active material is 4 to 8;

[0025] Preferably, the OI value of the second negative electrode active material is 2-5.

[0026] In one possible implementation, the negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon, graphene, titanium-based materials, silicon-based materials, tin-based materials, nitrides and metallic lithium;

[0027] In a possible implementation, the thickness H of the negative electrode active material layer is less than 400 μm;

[0028] In a possible implementation, the ultimate compaction density of the first negative electrode active material is 1.75 to 1.95 g / cm 3 ;

[0029] In a possible implementation, the ultimate compaction density of the second negative electrode active material is 1.2 to 1.78 g / cm 3 ;

[0030] In one possible embodiment, the particle size Dv50(1) of the first negative electrode active material is 5 μm to 15 μm;

[0031] In one possible implementation, the particle size Dv50(2) of the second negative electrode active material is 8 μm to 20 μm.

[0032] In a possible implementation manner, a groove region is provided on the surface of the negative electrode active material layer away from the current collector.

[0033] In a possible implementation manner, the depth h of the groove region satisfies: 0.05h n <h≤h n .

[0034] In a possible implementation, the groove area includes a plurality of linear grooves and / or a plurality of holes;

[0035] Preferably, the line width of the linear groove is 10 to 150 μm;

[0036] Preferably, the line depth including the linear groove is 3 to 30 μm;

[0037] Preferably, the pore size is 20 to 200 μm;

[0038] Preferably, the pores have a depth of 5 to 50 μm.

[0039] Several refers to one or more.

[0040] In a second aspect, the present application provides a lithium-ion battery, comprising the negative electrode plate.

[0041] The technical solution of this application has the following advantages:

[0042] 1. The present application provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer disposed on at least one surface of the current collector; the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a first negative electrode active material and a second negative electrode active material; the ultimate compaction density of the first negative electrode active material minus the ultimate compaction density of the second negative electrode active material = 0.01 to 0.75 g / cm 3 ; In the negative electrode active material layer, along the direction away from the current collector, the negative electrode active material layer includes n coating layers, 3≤n≤10, n is an integer; along the direction away from the current collector, the content of the first negative electrode active material in the n coating layers gradually decreases, and the content of the second negative electrode active material gradually increases.

[0043] The first negative electrode active material with a larger ultimate compaction density and a higher gram capacity is a negative electrode active material with a higher energy density, and the negative electrode material with a smaller ultimate compaction density and a lower gram capacity is a negative electrode active material with better kinetic performance. It is difficult for a single negative electrode active material to take into account both battery kinetics and high energy density requirements. Mixing two negative electrode active materials with high kinetics and high gram capacity can effectively solve the above problems.

[0044] This application adopts gradient coating technology, which can improve the uniformity of the first negative electrode active material and the second negative electrode active material per unit area, and avoid the problem of local black spots or lithium precipitation at the anode interface caused by single-layer mechanical mixed coating. At the same time, placing more of the second negative electrode active material with good kinetics on the surface of the negative electrode sheet is more conducive to improving the cycle stability. Compared with the double-layer coating technology, the gradient coating technology can further improve the distribution uniformity of the two negative electrode materials in the thickness direction, reduce the difference in viscosity and surface tension of the slurry between different numbers of layers, and reduce the transmission / diffusion impedance between two adjacent layers. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0046] Figure 1 Schematic diagram of the negative electrode;

[0047] Figure 2 Schematic diagram of the groove area on the surface of the negative electrode plate.

[0048] Reference numerals:

[0049] 1-current collector; 2-negative electrode active material layer; 3-groove area; Z-direction away from the current collector. DETAILED DESCRIPTION

[0050] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0051] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0052] In a first aspect, the present application provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer disposed on at least one surface of the current collector;

[0053] The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a first negative electrode active material and a second negative electrode active material;

[0054] The negative electrode active material satisfies: AB = 0.01-0.75 g / cm 3 ;

[0055] A is the limiting compaction density of the first negative electrode active material, and B is the limiting compaction density of the second negative electrode active material;

[0056] In the negative electrode active material layer, along the direction away from the current collector, the negative electrode active material layer includes n coating layers, 3≤n≤10, n is an integer;

[0057] Along the direction away from the current collector, the content of the first negative electrode active material in the n coating layers gradually decreases, and the content of the second negative electrode active material gradually increases.

[0058] In a possible implementation, the formula is satisfied: i =aln(i)+b;

[0059] Where i is the i-th layer of n coating layers, y i is the percentage of the first negative electrode active material in the i-th layer to the total mass of the negative electrode active material in the i-th layer;

[0060] Preferably, y1=1, y n =0; among the n coating layers, the coating layer close to the current collector is the first layer, and the coating layer far away from the current collector is the nth layer.

[0061] The total mass of the negative electrode active material refers to the sum of the masses of the first negative electrode active material and the second negative electrode active material in the i-th layer.

[0062] The ultimate compaction density refers to the maximum compaction that the material can withstand. It is usually observed during the rolling process whether the SEM particles are broken or the pole pieces are broken. The recommended compaction density of the material will be slightly lower than the ultimate compaction density by 0.02 to 0.05.

[0063] Regulate the proportion of the first negative electrode active material and the second negative electrode active material to build an efficient channel for ions and electrons, reduce the diffusion resistance of lithium ions, and slow down the battery capacity decay. i =aln(i)+b, achieving the outermost layer of the second negative electrode active material with good kinetics and stability, and the innermost layer of the first negative electrode active material with high compaction and high energy density, taking into account the core requirements of high safety performance, high energy density and high fast charging. The content ratio of the first negative electrode active material to the second negative electrode active material is y i / (1-y i ) range is (0, +∞).

[0064] a and b are constants, which can be obtained by replacing y1 and y n Substitute into the formula and calculate.

[0065] Exemplary:

[0066] The negative electrode active material layer includes 5 coating layers, that is, n=5; y1=1, y5=0, that is, the negative electrode active materials in the first layer are all the first negative electrode active materials, and the negative electrode active materials in the fifth layer are all the second negative electrode active materials. It is calculated that a=-0.621, b=1, that is, it satisfies:

[0067] y i =-0.621ln(i)+1.

[0068] In a possible implementation, along the direction away from the current collector, among the n coating layers, the thickness from the first coating layer to the (n+1) / 2th layer gradually decreases, and the thickness from the (n+1) / 2th layer to the nth layer gradually increases;

[0069] Preferably, the thickness h of the i-th layer i Satisfy: h i =di 2 +ei+f;

[0070] Preferably, h (n+1) / 2 =0, h1=h n ;

[0071] Preferably, h1 ≤ 130 μm.

[0072] In order to prevent the outermost layer of high-kinetic second negative electrode active material from being too thin and failing to take better account of the cycle stability, the thickness of the outermost coating layer (the second negative electrode active material content is the highest) is set to be larger; in order to maximize the overall energy density and rate performance of the battery cell, the thickness of the innermost coating layer with high compaction and high gram capacity (the first negative electrode active material content is the highest) is set to be larger. i =di 2 When +ei+f, the thickness of the first and nth negative electrode active layers can be made moderate, which can not only ensure higher dynamics, but also further improve the energy density of the battery, and further improve the overall energy density and safety performance of the battery cell.

[0073] d, e, and f are constants, which can be obtained by changing h1, h (n+1) / 2 and h n Substitute into the formula and calculate.

[0074] Optionally, the negative electrode active material layer includes n coating layers, and when n is an even number, h (n+1) / 2 =0; when n is an odd number, h (n+1) / 2 ≥5μm.

[0075] Exemplary:

[0076] The negative electrode active material layer includes 5 coating layers, that is, n=5; h3=5μm, h1=h5=100μm, d=23.75, e=-142.5, f=218.75 are calculated, that is, the following is satisfied:

[0077] h i =23.75i 2 -142.5i+218.75

[0078] In one possible embodiment, along the direction away from the current collector, the D50 of the n coating layers is i Gradually increase; D50 i is the average particle size of the negative electrode active material in the i-th layer, which is the particle size corresponding to the cumulative volume distribution of 50%, and can be obtained by testing with a laser particle size analyzer. Gradually increasing the particle size of the negative electrode active material away from the current collector can delay the consumption of the negative electrode film-forming additive in the electrolyte due to the small particle size of the surface negative electrode active material, thereby delaying the problem of black spot lithium precipitation in the battery cell caused by electrolyte bridge breakage.

[0079] Preferably, meeting: D50 i =gi+h; where g>0, h>0;

[0080] Preferably, D50 n -D501≤5μm;

[0081] g and h are constants. By n Substitute D501 into the formula to calculate. Exemplary:

[0082] The negative electrode active material layer includes 5 coating layers, that is, n=5; D501=10μm, D50 n =15μm, we get g=1.25, h=8.75, which satisfies:

[0083] D50 i =1.25i+8.75.

[0084] In one possible implementation, the negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon, graphene, titanium-based materials, silicon-based materials, tin-based materials, nitrides and metallic lithium;

[0085] In a possible implementation manner, the thickness H of the negative electrode active material layer is less than 400 μm.

[0086] In one possible implementation, the ultimate compaction density of the first negative electrode active material is 1.75 to 1.95 g / cm 3 ;

[0087] In a possible implementation, the ultimate compaction density of the second negative electrode active material is 1.6 to 1.78 g / cm 3 ;

[0088] In one possible implementation, XY≥3 mAh / g is satisfied;

[0089] X is the gram capacity of the first negative electrode active material, and Y is the gram capacity of the second negative electrode active material;

[0090] Preferably, the gram capacity of the first negative electrode active material is greater than 355 mAh / g;

[0091] Preferably, the gram capacity of the second negative electrode active material is ≤354 mAh / g;

[0092] In one possible embodiment, the first negative electrode active material is a graphite material, and the gram capacity of the first negative electrode active material is 357-360 mAh / g, preferably 357-360 mAh / g; the second negative electrode active material is a graphite material, and the gram capacity of the second negative electrode active material is 330-354 mAh / g, preferably 350-354 mAh / g.

[0093] In a possible implementation, the first negative electrode active material is a combination of a graphite material and a silicon material; the gram capacity of the silicon material is 1600 to 3000 mAh / g, preferably 1700 to 1800 mAh / g.

[0094] In a possible implementation, MN≥2 is satisfied;

[0095] M is the OI value of the first negative electrode active material, and N is the OI value of the second negative electrode active material;

[0096] Preferably, the OI value of the first negative electrode active material is 4 to 8;

[0097] Preferably, the OI value of the second negative electrode active material is 2 to 5;

[0098] The OI value (Orientation Index) is a parameter that describes the degree of order in a material. The OI value is calculated by analyzing the X-ray diffraction (XRD) pattern, specifically involving the ratio of the diffraction signals of the (002) and (004) crystal planes to the diffraction signal of the (110) crystal plane.

[0099] Graphite materials with large OI values ​​and high orientation usually have better conductivity and thermal stability, thereby improving the performance of lithium-ion batteries. With small OI values, as the orientation decreases, the ability to charge at high rates gradually increases.

[0100] In one possible embodiment, the particle size Dv50(1) of the first negative electrode active material is 5 μm to 15 μm;

[0101] In one possible implementation, the particle size Dv50(2) of the second negative electrode active material is 8 μm to 20 μm.

[0102] In one possible implementation, the first negative electrode active material supports a rate performance of 2C or less;

[0103] In one possible embodiment, the second negative electrode active material supports a rate performance of 2.5C and above;

[0104] In a possible implementation, artificial graphite as the first negative electrode active material is prepared from needle coke as a raw material;

[0105] In a possible implementation manner, artificial graphite used as the second negative electrode active material is prepared using petroleum coke as a raw material.

[0106] In a possible implementation manner, a groove region is provided on the surface of the negative electrode active material layer away from the current collector.

[0107] By forming an uneven groove area on the surface of the pole piece corresponding to the lithium precipitation area to improve the pore structure of the negative pole piece, the overall electrolyte infiltration effect and speed of the pole piece can be increased, and the storage space, storage volume and electrolyte retention capacity of the pole piece during a long cycle can be increased, effectively solving the problems of poor electrolyte infiltration and insufficient electrolyte in the late cycle of high-density and high-energy-density system batteries, thereby improving the power of the battery cell, and increasing the battery cycle life and capacity retention rate. At the same time, the negative pole piece is provided with a groove area, which can reduce the mechanical strength of the groove area, have elasticity, and can effectively alleviate the volume expansion caused by excessive compaction of the negative electrode, thereby effectively alleviating the expansion of the negative electrode during the charge and discharge process, and improving the safety and life of the lithium-ion battery. It can also enhance mass transfer, reduce ion impedance, and shorten the transmission distance of lithium ions.

[0108] In a possible implementation manner, the depth h of the groove region satisfies: 0.05h n <h≤h n .

[0109] The depth h of the groove area meets the above definition, which can significantly improve the interface problem. At the same time, it can prevent the groove area from being too deep to affect the protection of the outermost second negative electrode active material to the inner negative electrode active material, further improving the safety performance of the battery.

[0110] In a possible implementation manner, the groove area is made by laser punching;

[0111] Preferably, the line width is 10 to 150 μm;

[0112] Preferably, the line depth is 3 to 30 μm;

[0113] In a possible implementation manner, the groove area is made by laser drilling;

[0114] Preferably, the pore size is 20 to 200 μm;

[0115] Preferably, the hole depth is 5 to 50 μm.

[0116] In a second aspect, the present application provides a lithium-ion battery comprising the above-mentioned negative electrode plate.

[0117] Example 1

[0118] This embodiment provides a method for preparing a lithium ion battery, comprising:

[0119] (1) Preparation of negative electrode sheet:

[0120] The first negative electrode active material and the second negative electrode active material are both graphite, and the parameters of the two graphites are shown in Table 1:

[0121] Table 1

[0122]

[0123] In this embodiment, AB = 0.17 g / cm 3 , XY=10mAh / g, MN=2.

[0124] The negative electrode active material layer 2 is divided into 6 coating layers (such as Figure 1 As shown), h1=h6=100μm, h 3.5 =0 μm, y1=1, y6=0, in each coating layer, the mass content of the first negative electrode active material satisfies:

[0125] y i =-0.558ln(i)+1.

[0126] That is, y1=1, y2=0.61, y3=0.39, y4=0.23, y5=0.10, y6=0.

[0127] The thickness of each coating layer meets: h i =16i 2 -112i+196.

[0128] That is, h1=100 μm, h2=36 μm, h3=4 μm, h4=4 μm, h5=36 μm, and h6=100 μm.

[0129] Along the direction Z away from the current collector, D50 in n coating layers i Gradually increase. Limit D501 = 13μm, D506 = 17μm, and the thickness of each coating layer meets D50 i =0.8i+12.2.

[0130] That is, D501=13μm, D502=13.8μm, D503=14.6μm, D504=15.4μm, D505=16.2μm, D506=17μm.

[0131] In the first layer of the n coating layers (i.e., the layer close to the current collector), the mass ratio of the first negative electrode active material, the second negative electrode active material, the conductive agent, and the binder is 98.2:0:0.6:1.2; the mass ratio in the second layer is 60.2:38.0:0.6:1.2, the mass ratio in the third layer is 38.0:60.2:0.6:1.2, the mass ratio in the fourth layer is 22.2:76.0:0.6:1.2, the mass ratio in the fifth layer is 10.0:88.2:0.6:1.2, and the mass ratio in the sixth layer is 0:98.2:0.6:1.2.

[0132] The slurries of the coating layers are prepared respectively, and are coated on the negative electrode current collector copper foil in sequence along the direction Z away from the current collector.

[0133] The above product is then rolled and cut. Lines are made on the surface of the negative electrode active material layer to obtain Figure 2 The groove area 3 shown has a center distance of 150 μm between two adjacent lines, a line depth of 5 μm, and a line width of 15 μm, thereby obtaining a negative electrode sheet.

[0134] (2) Preparation of positive electrode sheet:

[0135] Using NCM613 ternary material particles as the positive electrode active material, the conductive agent and the binder were added into a stirring tank at a mass ratio of 97.4:1.4:1.2 to prepare the positive electrode slurry. The positive electrode slurry was coated on aluminum foil using a coating machine, dried at 100°C, and then rolled and cut to obtain the positive electrode sheet.

[0136] The positive electrode sheet and negative electrode sheet prepared above are wound together with a separator to form a battery cell, which is then packaged with an aluminum plastic film, baked to remove moisture, and then injected with electrolyte, and then processed by formation, secondary sealing, etc. to obtain a lithium-ion battery.

[0137] Example 2

[0138] This embodiment is substantially the same as the embodiment 1, except that the negative electrode active material layer includes three coating layers.

[0139] At this time, in each coating layer, the mass content of the first negative electrode active material satisfies:

[0140] y i =-0.91ln(i)+1.

[0141] That is, y1=1, y2=0.37, y3=0.

[0142] The thickness of each coating layer meets: h i =95i 2 -380i+385.

[0143] That is, h1=100 μm, h2=5 μm, h3=100 μm.

[0144] In the direction away from the current collector, the D50 of n coating layers i Gradually increase. Limit D501 = 13μm, D503 = 17μm, and the thickness of each coating layer meets D50 i =2i+11.

[0145] That is, D501=13μm, D502=15μm, D503=17μm.

[0146] In the first layer of the n coating layers (i.e., the layer close to the current collector), the mass ratio of the first negative electrode active material, the second negative electrode active material, the conductive agent, and the binder is 98.2:0:0.6:1.2; the mass ratio in the second layer is 36.3:61.9:0.6:1.2, and the mass ratio in the third layer is 0:98.2:0.6:1.2.

[0147] Example 3

[0148] This embodiment is substantially the same as Embodiment 1, except that the negative electrode active material layer includes 10 coating layers.

[0149] At this time, in each coating layer, the mass content of the first negative electrode active material satisfies:

[0150] y i =-0.434ln(i)+1.

[0151] That is, y1=1, y2=0.70, y3=0.52, y4=0.40, y5=0.30, y6=0.22, y7=0.16, y8=0.10, y9=0.05, y 10 =0.

[0152] The thickness of each coating layer meets: h i =4.9383i 2 -54.321i+149.38.

[0153] That is, h1=100μm, h2=60.5μm, h3=30.9μm, h4=11.1μm, h5=1.2μm, h6=1.2μm, h7=11.1μm, h8=30.9μm, h9=60.5μm, h 10 =100μm.

[0154] In the direction away from the current collector, the D50 of n coating layers i Gradually increase. Limit D501 = 13μm, D50 10 =17μm, the thickness of each coating layer meets D50 i =0.4444i+12.556.

[0155] That is, D501 = 13 μm, D502 = 13.4 μm, D503 = 13.9 μm, D504 = 14.3 μm, D505 = 14.8 μm, D506 = 15.2 μm, D507 = 15.7 μm, D508 = 16.1 μm, D509 = 16.6 μm, D50 10 =17μm.

[0156] In the first layer of the n coating layers (i.e., the layer close to the current collector), the mass ratio of the first negative electrode active material, the second negative electrode active material, the conductive agent, and the binder is 98.2:0:0.6:1.2; the mass ratio in the second layer is 68.7:29.5:0.6:1.2, the mass ratio in the third layer is 51.4:46.8:0.6:1.2, the mass ratio in the fourth layer is 39.1:59.1:0.6:1.2, and the mass ratio in the fifth layer is 10.8:1:0.6:1.2. The mass ratio is 29.6:68.6:0.6:1.2, the mass ratio in the 6th layer is 21.8:76.4:0.6:1.2, the mass ratio in the 7th layer is 15.3:82.9:0.6:1.2, the mass ratio in the 8th layer is 9.6:88.6:0.6:1.2, the mass ratio in the 9th layer is 4.6:93.6:0.6:1.2, and the mass ratio in the 10th layer is 0:98.2:0.6:1.2.

[0157] Example 4

[0158] This embodiment is basically the same as Embodiment 1, except that the parameters of the first negative electrode active material and the second negative electrode active material are shown in Table 2.

[0159] Table 2

[0160]

[0161] In this embodiment, AB = 0.55 g / cm 3 , XY=6mAh / g, MN=2.3.

[0162] Example 5

[0163] This embodiment is basically the same as Embodiment 1, except that the parameters of the first negative electrode active material and the second negative electrode active material are shown in Table 3.

[0164] Table 3

[0165]

[0166]

[0167] In this embodiment, AB = 0.02 g / cm 3 , XY=6mAh / g, MN=2.

[0168] Example 6

[0169] This embodiment is substantially the same as the embodiment 1, except that in this embodiment, y1=1, y6=0.1 are defined, and the mass content of the first negative electrode active material satisfies:

[0170] y i=-0.502ln(i)+1.

[0171] That is, y1=1, y2=0.65, y3=0.45, y4=0.30, y5=0.19, y6=0.1.

[0172] Example 7

[0173] This embodiment is substantially the same as the embodiment 1, except that, in this embodiment, y1=0.9, y6=0, and the mass content of the first negative electrode active material satisfies:

[0174] y i =-0.502ln(i)+0.9.

[0175] That is, y1=0.9, y2=0.55, y3=0.35, y4=0.20, y5=0.09, y6=0.

[0176] Example 8

[0177] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, y1=1, y2=0.8, y3=0.7, y4=0.6, y5=0.5, y6=0.4.

[0178] Example 9

[0179] This embodiment is basically the same as the embodiment 1, except that in this embodiment, y is defined as h1=h6=80 μm, h 3.5 =0μm.

[0180] The thickness of each coating layer meets: h i =12.8i 2 -89.6i+156.8.

[0181] That is, h1 = 80 μm, h2 = 28.8 μm, h3 = 3.2 μm, h4 = 3.2 μm, h5 = 28.8 μm, and h6 = 80 μm.

[0182] Example 10

[0183] This embodiment is basically the same as the embodiment 1, except that in this embodiment, y is defined as h1=h6=60 μm, h 3.5 =0μm.

[0184] The thickness of each coating layer meets: h i =9.6i 2 -67.2i+117.6.

[0185] That is, h1 = 60 μm, h2 = 21.6 μm, h3 = 2.4 μm, h4 = 2.4 μm, h5 = 21.6 μm, and h6 = 60 μm.

[0186] Embodiment 11

[0187] This embodiment is substantially the same as the first embodiment, except that h1 = 100 μm, h2 = 70 μm, h3 = 30 μm, h4 = 50 μm, h5 = 90 μm, and h6 = 100 μm.

[0188] Example 12

[0189] This embodiment is basically the same as the embodiment 1, except that in this embodiment, D501 is limited to 15 μm, D506 is limited to 20 μm, and the thickness of each coating layer satisfies D50 i =i+14.

[0190] That is, D501=15μm, D502=16μm, D503=17μm, D504=18μm, D505=19μm, D506=20μm.

[0191] Example 13

[0192] This embodiment is basically the same as the embodiment 1, except that in this embodiment, D501 is limited to 5 μm, D506 is limited to 10 μm, and the thickness of each coating layer satisfies D50 i =i+4.

[0193] That is, D501=5μm, D502=6μm, D503=7μm, D504=8μm, D505=9μm, D506=10μm.

[0194] Embodiment 14

[0195] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, D501 = 13 μm, D502 = 15 μm, D503 = 15.8 μm, D504 = 16 μm, D505 = 16.5 μm, and D506 = 17 μm.

[0196] Embodiment 15

[0197] This embodiment is substantially the same as the embodiment 1, except that, in this embodiment, the depth of the wires punched on the surface of the negative electrode active material layer is 5 μm.

[0198] Example 16

[0199] This embodiment is substantially the same as the embodiment 1, except that, in this embodiment, the depth of the wires punched on the surface of the negative electrode active material layer is 100 μm.

[0200] Embodiment 17

[0201] This embodiment is substantially the same as the embodiment 1, except that, in this embodiment, the depth of the wires punched on the surface of the negative electrode active material layer is 150 μm.

[0202] Embodiment 18

[0203] This embodiment is basically the same as the embodiment 1, except that the negative electrode plate of this embodiment is not provided with a groove area (ie, no wire bonding is performed).

[0204] Comparative Example 1

[0205] This comparative example is basically the same as Example 1, except that the negative electrode plate is prepared by mechanical mixing single layer coating.

[0206] Comparative Example 2

[0207] This comparative example is basically the same as Example 1, except that a double-layer coating technology is used to prepare the negative electrode sheet. Two coating layers are provided on the negative electrode current collector, and in the first layer, the mass ratio of the first negative electrode active material, the conductive agent, and the binder is 98.2:0.6:1.2; in the second layer, the mass ratio of the second negative electrode active material, the conductive agent, and the binder is 98.2:0.6:1.2.

[0208] Test Case

[0209] 1. Ultimate compaction density test:

[0210] Ultimate compaction density = surface density / material thickness

[0211] (1) Cut the electrode sheet with a size of 300 mm × 250 mm using a paper cutter, measure the thickness of the electrode sheet at three different positions, and select the electrode sheet with a thickness error of less than 3 μm as the experimental sheet;

[0212] (2) Use a circular sampler to cut out three pieces of 100 cm2 at different positions of the original electrode sheet described in step (1). 2 Weigh the weight of the cut electrode sheet and current collector, take the average value as M0 and M1, and calculate the electrode sheet surface density: S = (M0-M1) / 100cm 2 ;

[0213] (3) Setting the linear speed of the double rollers of the rolling mill to 2.0 m / min, setting the rolling pressure to 1.3 MPa as the starting value, and after the pressure stabilizes, placing the electrode sheet selected in step (1) for rolling, and increasing the rolling pressure in increments of 0.65 MPa until waves appear on both sides of the electrode sheet and vertical lines appear in the middle of the electrode sheet, which is the ultimate compaction density of the material under this system;

[0214] (4) Use a micrometer to measure the thickness of the electrode sheet at three different positions after rolling at different pressures, and record them as L1, L2, and L3. If the value difference between any two of the three positions is 3 μm or more, it is considered an unqualified sheet. Record the thickness of the qualified electrode sheet and take the average value as Li. Then use a micrometer to measure the thickness of the current collector after rolling, and record it as Lo. The ultimate compaction density is calculated by the formula: P = S / (Li-Lo).

[0215] 2. Furnace temperature test:

[0216] At 25℃±3℃, discharge the battery at 0.2C to a cut-off voltage of 3.0V; let it stand for 5 minutes; charge it at 0.5C constant current and constant voltage to the upper limit voltage, with a cut-off current of 0.05C; test the voltage, internal resistance, and thickness of the fully charged state at 25℃±3℃, and take pictures before the test; put the fully charged battery into the test box, and heat the test box at a temperature rise rate of (5±2)℃ / min. When the temperature in the box reaches 140℃±2℃, keep the temperature constant for 60 minutes; after the test is completed, test the voltage and internal resistance on the platform, and take pictures after the test. If there is no fire or explosion, it is considered to have passed the furnace temperature test.

[0217] 3. Cycle test:

[0218] The cycle test was carried out at 25℃±5℃ for 1000T, and the test conditions were 2C-3.5V (1C cut-off) to 1C-3.65V (0.05C cut-off) / 0.5C-2.5V. The discharge capacity of each cycle was monitored online, and the capacity retention rate was calculated.

[0219] 4. Disassemble the fully charged batteries with 300T and 600T cycles and observe whether black spots appear on the anode interface.

[0220] 5. The test method for battery rate performance is:

[0221] Let the battery stand for 10 minutes at 25±5℃; discharge at 0.2C to 3.0V, let stand for 10 minutes; charge at a certain rate (0.2C / 0.3C / 0.4C...), cut-off current 0.05C, let stand for 10 minutes, discharge at 0.5C to 3.0V; let stand for 10 minutes. After 30 cycles of the above steps, the battery is fully charged and disassembled. Observe the anode interface. If the anode electrode is golden and there is no abnormality, there is no lithium deposition, which means that the battery supports the corresponding rate performance; if there are gray / brown / white particles covering the interface, the battery has lithium deposition, and does not support the corresponding rate performance at this time. The maximum rate at which the battery does not deposit lithium is the rate performance of the battery. Among them, the rate performance is good if it is above 1.5. Good rate performance is the standard for batteries to leave the factory.

[0222] The test results are shown in Table 4.

[0223] Table 4

[0224]

[0225]

[0226] From the comparison of the examples and comparative examples in Table 1, it can be seen that the present application can avoid the problem of local black spots or lithium deposition on the anode interface, while improving the cycle stability, and the rate performance of the lithium-ion battery is also significantly improved.

[0227] From the comparison of Example 1, Example 6, Example 7 and Example 8, it can be seen that the formula y is satisfied i =aln(i)+b can further improve the cycle performance and rate performance of the battery.

[0228] By comparing Example 1, Example 9, Example 10 and Example 11, it can be seen that the formula h is satisfied. i =di 2 +ei+f can further improve the cycle performance and rate performance of the battery.

[0229] From the comparison of Example 1, Example 12, Example 13 and Example 14, it can be seen that the formula D50 is satisfied. i =gi+h can further improve the battery's cycle performance and rate performance.

[0230] From the comparison of Example 1, Example 15, Example 16 and Example 17, it can be seen that the 0.05h n <h≤h n The cycle performance and rate performance of the battery can be further improved.

[0231] From the comparison between Example 1 and Example 18, it can be seen that providing a groove area in the negative electrode plate can further improve the cycle performance and rate performance of the battery.

[0232] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection created by this application.

Claims

1. A negative electrode plate, characterized in that: comprising a current collector and a negative electrode active material layer disposed on at least one surface of the current collector; The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a first negative electrode active material and a second negative electrode active material; The negative electrode active material satisfies: AB = 0.01-0.75 g / cm 3 ; A is the limiting compaction density of the first negative electrode active material, and B is the limiting compaction density of the second negative electrode active material; In the negative electrode active material layer, along the direction away from the current collector, the negative electrode active material layer includes n coating layers, 3≤n≤10, n is an integer; Along the direction away from the current collector, the content of the first negative electrode active material in the n coating layers gradually decreases, and the content of the second negative electrode active material gradually increases.

2. The negative electrode sheet according to claim 1, characterized in that: Along the direction away from the current collector, among the n coating layers, the thickness of the first layer to the (n+1) / 2th layer gradually decreases, and the thickness of the (n+1) / 2th layer to the nth layer gradually increases; the coating layer close to the current collector is the first layer, and the coating layer away from the current collector is the nth layer; Preferably, the thickness h of the (n+1) / 2th layer is (n+1) / 2 = 0, the thickness of the first layer h1 = the thickness of the nth layer h n ; Preferably, h1≤130 μm.

3. The negative electrode sheet according to claim 1, characterized in that: In the direction away from the current collector, the D50 i Gradually increase; D50 i is the average particle size of the negative electrode active material in the i-th layer; Preferably, D50 n -D501≤5μm.

4. The negative electrode sheet according to claim 1, characterized in that: Satisfy XY≥3mAh / g; X is the gram capacity of the first negative electrode active material, and Y is the gram capacity of the second negative electrode active material; Preferably, the gram capacity of the first negative electrode active material is greater than 355 mAh / g; Preferably, the gram capacity of the second negative electrode active material is ≤354 mAh / g.

5. The negative electrode sheet according to claim 1, characterized in that: Satisfy MN ≥ 2; M is the OI value of the first negative electrode active material, and N is the OI value of the second negative electrode active material; Preferably, the OI value of the first negative electrode active material is 4 to 8; Preferably, the OI value of the second negative electrode active material is 2-5.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is met: (1) The negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon, graphene, titanium-based materials, silicon-based materials, tin-based materials, nitrides and metallic lithium; (2) The thickness H of the negative electrode active material layer is less than 400 μm; (3) The ultimate compaction density of the first negative electrode active material is 1.75 to 1.95 g / cm 3 ; (4) The ultimate compaction density of the second negative electrode active material is 1.2 to 1.78 g / cm 3 ; (5) The particle size Dv50(1) of the first negative electrode active material is 5 μm to 15 μm; (6) The particle size Dv50(2) of the second negative electrode active material is 8 μm to 20 μm.

7. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: A groove area is arranged on the surface of the negative electrode active material layer away from the current collector.

8. The negative electrode sheet according to claim 7, characterized in that: The depth h of the groove area satisfies: 0.05h n <h≤h n .

9. The negative electrode sheet according to claim 7, characterized in that: The groove area includes a plurality of linear grooves and / or a plurality of holes; Preferably, the line width of the linear groove is 10 to 150 μm; Preferably, the line depth including the linear groove is 3 to 30 μm; Preferably, the pore size is 20 to 200 μm; Preferably, the hole depth is 5 to 50 μm; Several refers to one or more.

10. A lithium ion battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative plate and battery

    CN113555526A

  • Negative pole piece and lithium ion battery

    CN114079048A

  • Lithium battery negative pole piece and lithium battery

    CN114335419A

  • Negative plate and application thereof

    CN115295783A

  • Negative plate, secondary battery and electric equipment

    CN117317127A

Cited By

  • Negative pole piece, preparation method thereof and lithium ion battery

    CN121460494A